Viscous Chaplygin Gas In f(G) Theory Of Gravity - Hatkar, S. P.; Agre, P. A.; Tadas, D. P.; Katore, S. D.; Pawar, D. D.
In this paper, we have considered Friedmann-Robertson-Walker space-time in the context of f(G) theory of gravitation. The viscosity in presence of Chaplygin gas is taken as source of matter. Field equations are solved by using linearly varying deceleration parameter. Statefinder diagnostic pair {r, s} is also investigated. It is found that the model is stable.
Keywords: Gravitation